STAT3‐induced upregulation of lncRNA ABHD11‐AS1 promotes tumour progression in papillary thyroid carcinoma by regulating miR‐1301‐3p/STAT3 axis and PI3K/AKT signalling pathway. (18th January 2019) - Wen, Juyi; Wang, Hongwei; Dong, Tingjun; Gan, Panpan; Fang, Henghu; Wu, Sudong; Li, Jingjiao; Zhang, Yuanyuan; Du, Rui; Zhu, Qi
Abstract: Objectives: Emerging evidences indicated the importance of long non‐coding RNAs (lncRNAs) in the tumorigenesis and deterioration of malignant tumours. To our knowledge, the study about lncRNAs in papillary thyroid carcinoma (PTC) is still inadequate. ABHD11‐AS1 was highly expressed in the PTC samples of The Cancer Genome Atlas database. This study focused on the biological function and mechanism of lncRNA ABHD11‐AS1 in PTC. Materials and methods: qRT‐PCR analysis was used to examine the expression of ABHD11‐AS1 in PTC tissues and cell lines. The prognostic significance of ABHD11‐AS1 for the patients with PTC was analysed with Kaplan‐Meier analysis. The effects of ABHD11‐AS1 knockdown on the cell proliferation and metastasis were evaluated by in vitro functional assays and in vivo experiments. The molecular mechanism which contributed to the oncogenic role of ABHD11‐AS1 in PTC was explored by conducting mechanism experiments. Rescue assays were carried out for final demonstration. Results: High expression of ABHD11‐AS1 predicted poor prognosis for patients with PTC and promoted cell proliferation and metastasis in vitro and in vivo. ABHD11‐AS1 was activated by the transcription factor STAT3. ABHD11‐AS1 positively regulated PI3K/AKT signalling pathway. ABHD11‐AS1 acted as a competitive endogenous (ce) RNA to upregulate STAT3 by sponging miR‐1301‐3p. Conclusions: STAT3‐induced lncRNA ABHD11‐AS1 promoted PTC progression by regulating PI3K/AKT signalling pathway and miR‐1301‐3p/STAT3 axis.